2014
DOI: 10.1007/s12275-014-4113-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antimicrobial potency of silver nanoparticles biosynthesized by using an endophytic fungus, Cryptosporiopsis ericae PS4

Abstract: In the present study, silver nanoparticles (AgNPs) with an average particle size of 5.5 ± 3.1 nm were biosynthesized using an endophytic fungus Cryptosporiopsis ericae PS4 isolated from the ethno-medicinal plant Potentilla fulgens L. The nanoparticles were characterized using UV-visible spectrophotometer, transmission electron microscopy (TEM), scanning electron microscopy (SEM), selective area electron diffraction (SAED), and energy dispersive X-ray (EDX) spectroscopy analysis. Antimicrobial efficacy of the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 36 publications
2
19
0
1
Order By: Relevance
“…Studies have found that Ag-NPs with a size of 5-20 nm had greater antibacterial activities [2][3][4]. Currently, the widely recognized antibacterial mechanisms of Ag-NPs include disrupting the normal function of the cell wall [5], interacting with the lipid components of the cell membrane to impede its normal function [6][7][8][9][10], inducing ROS free radicals to damage the cell membrane [11][12][13], damaging the DNA structure and inhibiting its related functions [14][15][16], binding with sulfhydryl groups of enzyme proteins to make cell inactive, and so on [17,18]. Ag-NPs inhibits the characteristics of simple preparation, broad-spectrum antibacterial, strong sterilization, and less prone to emerge drug resistance, which prompted it to be used as an antibacterial agent added to ceramics [19], coatings [20], textiles [21], films [22,23], and other raw materials to fabricate antibacterial materials.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that Ag-NPs with a size of 5-20 nm had greater antibacterial activities [2][3][4]. Currently, the widely recognized antibacterial mechanisms of Ag-NPs include disrupting the normal function of the cell wall [5], interacting with the lipid components of the cell membrane to impede its normal function [6][7][8][9][10], inducing ROS free radicals to damage the cell membrane [11][12][13], damaging the DNA structure and inhibiting its related functions [14][15][16], binding with sulfhydryl groups of enzyme proteins to make cell inactive, and so on [17,18]. Ag-NPs inhibits the characteristics of simple preparation, broad-spectrum antibacterial, strong sterilization, and less prone to emerge drug resistance, which prompted it to be used as an antibacterial agent added to ceramics [19], coatings [20], textiles [21], films [22,23], and other raw materials to fabricate antibacterial materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is a result from their evolutionary processes occurring in the course of an antibiotic treatment. The resistant bacteria survive medical treatment and pass this trait to future generations [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…However, complete inhibition of the growth of C. albicans MTCC183 was found at a concentration of 10 μM AgNPs. 264 A more recent report showed that AgNPs (spherical, 1-40 nm) had excellent antifungal activity against R. solani cultures by inhibiting 83% of the mycelium growth at 25 μg/mL concentration. 265 In another study, several essential oils were tested for their antifungal activity.…”
mentioning
confidence: 99%